2018
DOI: 10.1007/s10096-018-3187-9
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen-specific leptospiral proteins in urine of patients with febrile illness aids in differential diagnosis of leptospirosis from dengue

Abstract: Leptospirosis and dengue are two commonly seen infectious diseases of the tropics. Differential diagnosis of leptospirosis from dengue fever is often difficult due to overlapping clinical symptoms and lack of economically viable and easy-to-perform laboratory tests. The gold standard for diagnosis is the microscopic agglutination test (MAT). In this study, the diagnostic potential of screening for pathogen-specific leptospiral antigens in urine samples is presented as a non-invasive method of disease diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Clinical diagnosis of leptospirosis is also nonspecific mimicking other common infections, including dengue and malaria, which require further laboratory confirmation (Chaurasia et al 2018). In several places, including Brazil, Hawaii, Korea, New Caledonia, and Seychelles, Plank and Dean (2000) reported that common leptospirosis manifestations were fever, myalgia, headache, jaundice, and conjunctival suffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical diagnosis of leptospirosis is also nonspecific mimicking other common infections, including dengue and malaria, which require further laboratory confirmation (Chaurasia et al 2018). In several places, including Brazil, Hawaii, Korea, New Caledonia, and Seychelles, Plank and Dean (2000) reported that common leptospirosis manifestations were fever, myalgia, headache, jaundice, and conjunctival suffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Because an RDT capable of diagnosing leptospirosis using urine will be useful in remote health centres and large outbreaks situations, several studies have focused on the urine by targeting structural leptospiral antigens, such as lipopolysaccharides [10] ; outer membrane proteins LigA [11] , LipL32 [21] or DNA [22] . More recently, Chaurasia et al., detected additional pathogen specific antigens (LipL41, Fla1, HbpA and sphingomielinase) in the urine of leptospirosis patients collected in Kerala, India [23] . These antigens were also detected in patients with pyrexia of unknown origin with MAT-negative results.…”
Section: Discussionmentioning
confidence: 99%
“…L. interrogans expresses sph2 in dialysis membrane chambers implanted into 41 the peritoneal cavity of rats. Additionally, antisera raised against Sph2 detects antigen in kidney 42 sections from acutely-infected hamsters (11) and in urine obtained from leptospirosis patients 43 (12). Sph2 may contribute to the pathogenesis of leptospirosis by adhering to fibronectin, 44 inducing apoptosis of host cells, and triggering the production of proinflammatory cytokines (13-45 16).…”
Section: Introduction 29mentioning
confidence: 99%